Pengujian Kualitas Aplikasi Web E-Learning Universitas Pamulang Menggunakan Metode Black Box - Fefbi Septa Kristara; Gusti Kanuraga; Rohmat Rohmat; Dedi Yansah; Aries Saifudin; Yulianti Yulianti (Jurnal Informatika Universitas Pamulang, 2021)
A website will always have vulnerabilities in its system. One of the vulnerabilities that often occur on a website is an input validation problem or error handling that usually occurs in an input form. Testing on the Pamulang University e-learning website is important to guarantee that the software produced is meet the requirements. This test is doing to measure how good is the quality of the Pamulang University e-learning website. Good quality service will give satisfaction to students as users who benefit the most from the website. Testing the Pamulang University e-learning website is done using the black box testing method with the fuzzing technique approach. This technique can display complete information regarding the response from the server when the input form is giving abnormal data. The information obtained will later be analyzed to determine possible vulnerabilities.